2009
DOI: 10.1161/strokeaha.108.544866
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Outcomes and Appropriateness of Carotid Endarterectomy

Abstract: Background and Purpose-Prior work documented racial and ethnic disparities in incidence of stroke, stroke risk factors, and use of carotid endarterectomy. Less is known about disparities in outcomes and appropriateness of carotid endarterectomy or reasons for such inequalities. Methods-This was a population-based cohort of carotid endarterectomy performed in Medicare beneficiaries in New York. Clinical data were abstracted from medical charts to assess sociodemographics, clinical indication for carotid endarte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…16 This increase in emergent presentations is undesirable for both the patient and the health care system, as it may contribute to higher overall health care cost and resource utilization. Becker 17 showed in a 10-year analysis of patients with uterine fibroids that patients of non-white race/ethnicity had higher total cost and length of stay compared to white patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 This increase in emergent presentations is undesirable for both the patient and the health care system, as it may contribute to higher overall health care cost and resource utilization. Becker 17 showed in a 10-year analysis of patients with uterine fibroids that patients of non-white race/ethnicity had higher total cost and length of stay compared to white patients.…”
Section: Discussionmentioning
confidence: 99%
“…Low SES patients were treated at hospitals with less experience with the disease than high SES patients (mean 61 vs. 70, p<0.0001). The mean number of cases of diverticular disease treated by an individual attending physician was 3.3 (median, 2; range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Low SES patients were also treated by attending physicians with less experience than high SES patients (mean, 3 …”
Section: Provider and Hospital Volumementioning
confidence: 99%
“…[7][8][9][10][11] Although these studies identify differences in postprocedural outcomes related to race and ethnicity, they do not provide information about other racial groups, such as Asians and American Indians. In addition, these studies do not provide important information on medication use, carotid lesion anatomic factors, or recurrent stenosis, which are factors known to have significant impact on clinical outcomes after carotid revascularization.…”
Section: June 2015mentioning
confidence: 99%
“…3 Although some studies have identified disparate patterns of utilization of carotid imaging and surgical revascularization between patients from different racial or ethnic backgrounds, [3][4][5][6] other studies have not confirmed these findings. 7 The studies that did demonstrate racial differences also found higher mortality rates after CEA in blacks and Hispanics; 4,[8][9][10][11][12] and some studies showed a relative increase in the incidence of postprocedural stroke and myocardial infarction (MI) in blacks after CEA. 9,13 In a recent study analyzing a nationwide inpatient sample (NIS) from 2005 to 2008, postprocedural mortality was significantly higher in Hispanic and blacks than in whites after CEA but not after CAS.…”
mentioning
confidence: 99%
“…2 Explanations for these outcomes disparities have included increased comorbidities preoperatively, poor patient selection, confounding by socioeconomic status and other non-medical factors, and increased proportion of CEA operations on black patients performed at low volume institutions, by less experienced surgeons. 2, 6, 9, 11, 15 …”
Section: Introductionmentioning
confidence: 99%